Telecommunication cable : Self supporting drop wire. (Department of Standards Malaysia, 2012)
This Malaysian Standard specifies the construction, dimension and test requirements for self supporting drop wire. The cables as prescribed are generally used as outdoor telephone drop wire and used as telephone internal cabling for home if the steel wire is removed.